1997
DOI: 10.1128/mcb.17.4.2166
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptors and Retinoic Acid Receptors Differentially Control the Interactions of Retinoid X Receptor Heterodimers with Ligands, Coactivators, and Corepressors

Abstract: As the obligate member of most nuclear receptor heterodimers, retinoid X receptors (RXRs) can potentially perform two functions: cooperative binding to hormone response elements and coordinate regulation of target genes by RXR ligands. In this paper we describe allosteric interactions between RXR and two heterodimeric partners, retinoic acid receptors (RARs) and peroxisome proliferator-activated receptors (PPARs); RARs and PPARs prevent and permit activation by RXR-specific ligands, respectively. By competing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(180 citation statements)
references
References 60 publications
9
168
0
3
Order By: Relevance
“…The composite motif derived from in vivo DR1 elements illustrates that the spacer position favors adenosine, and the 3Ј half-site is more highly conserved. This is consistent with observations in vitro that RXR␣, which occupies the 3Ј half-site (DiRenzo et al 1997), has higher sequence stringency compared to PPAR␥ occupying the 5Ј site (Temple et al 2005). Although previous studies have suggested the existence of a conserved extended 5Ј sequence (IJpenberg et al 1997;Temple et al 2005), we did not find a strong preference.…”
Section: Discussionsupporting
confidence: 93%
“…The composite motif derived from in vivo DR1 elements illustrates that the spacer position favors adenosine, and the 3Ј half-site is more highly conserved. This is consistent with observations in vitro that RXR␣, which occupies the 3Ј half-site (DiRenzo et al 1997), has higher sequence stringency compared to PPAR␥ occupying the 5Ј site (Temple et al 2005). Although previous studies have suggested the existence of a conserved extended 5Ј sequence (IJpenberg et al 1997;Temple et al 2005), we did not find a strong preference.…”
Section: Discussionsupporting
confidence: 93%
“…This did not translate into a corresponding difference in N-CoR protein levels as assayed by immunoblotting. However, in an individual cell, co-activators and co-repressors can be recruited by different transcription factors and since they are generally not abundant, a measurement of the absolute amount does not exclude the possibility that varying amounts are available to the particular transcription factor PPARG [18].…”
Section: Discussionmentioning
confidence: 99%
“…An additional 200 μl of PBS buffer (137 mmol/l NaCl, 2.7 mmol/l KCl, 10 mmol/l Na 2 HPO 4 , 1.8 mmol/l KH 2 PO 4 , pH 7.5) containing 2 μg pAOX-Luc [18] and 0.1 μg pRluc plasmid (BioSignal, Packard, CT, USA) DNA was then mixed with the cells to allow determination of PPRE activity. The activity of a transfected human PPARG receptor was measured in the corresponding manner by using a construct of human PPARG ligand-binding domain fused to the yeast GAL4 DNA-binding domain [19], kindly provided by B. Staels (UR 545 INSERM, Institut Pasteur de Lille, Lille, France), and a plasmid encoding firefly luciferase under control of five copies of a GAL4 response element (5×GAL4-TK-LUC) (2 μg of each construct/cuvette) [20].…”
Section: Methodsmentioning
confidence: 99%
“…A similar adipogenic effect of TZDs has been observed using cultured bone marrow stromal cells (37). 4 Moreover, forced overexpression of PPAR␥ in fibroblasts (18) or cultured myoblasts (17) is sufficient to drive adipocyte differentiation. The role of the other PPAR isoforms in adipogenesis, however, is less clear.…”
Section: Resultsmentioning
confidence: 99%